2019
DOI: 10.3390/ani9121056
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance of Broilers as Influenced by Different Levels and Sources of Methionine Plus Cysteine

Abstract: Simple Summary: The current work evaluated the utilization of different sources of methionine either from DL-methionine (DL-Met) or L-methionine (L-Met) using different concentrations of dietary methionine plus cystine (Met + Cyst) in broiler chickens. Results showed that a better edible meat yield could be obtained by supplementing Met + Cyst at the rate of 80% of the digestible lysine.Abstract: The objective of this work was to evaluate the utilization of methionine from DL-methionine (DL-Met) and L-methioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
33
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 43 publications
12
33
1
3
Order By: Relevance
“…This experiment demonstrates that increasing diet DSAAs level up to 1.02% improved breast growth (Table 4). Our finding confirms previous studies, which reported Met supplementation improves protein synthesis and muscularity, where dietary supplementation of Met has a significant influence on breast weight (Schutte et al 1997;Nukreaw et al 2011;Yoo et al 2017;Rehman et al 2019). Del Vesco and Gasparino (2013) reported insulin-like growth factor-1 (IGF-1) gene expression in the liver was higher in animals fed extra Met.…”
Section: Carcase and Visceral Organ Relative Weightsupporting
confidence: 91%
See 1 more Smart Citation
“…This experiment demonstrates that increasing diet DSAAs level up to 1.02% improved breast growth (Table 4). Our finding confirms previous studies, which reported Met supplementation improves protein synthesis and muscularity, where dietary supplementation of Met has a significant influence on breast weight (Schutte et al 1997;Nukreaw et al 2011;Yoo et al 2017;Rehman et al 2019). Del Vesco and Gasparino (2013) reported insulin-like growth factor-1 (IGF-1) gene expression in the liver was higher in animals fed extra Met.…”
Section: Carcase and Visceral Organ Relative Weightsupporting
confidence: 91%
“…There are contradictory results on the effect of SAA on feed consumption. For example, our result resembles who observed no effect of diet Met levels on feed intake in broiler chickens (Dilger and Baker 2007;Goulart et al 2011; Rehman et al 2019;Zarghi et al 2020b). In contrast, reported Met deficiencies depressed the FI in broilers (Conde-Aguilera et al 2013).…”
Section: Growth Performancesupporting
confidence: 88%
“…The best strategy to optimize production and reproduction in poultry species while also mitigating the harmful results of environmental conditions is proper nutrition [ 1 , 2 , 3 ]. One of the pillars of nutrition is the use of amino acids in poultry diets.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic sources of methionine such as DL-methionine (DL-Met) are included in poultry feed to optimize the dietary level of methionine. Methionine plays an essential role in energy production and boosts the livability, performance and feed efficiency utilization in poultry [ 2 , 6 ]. Kidd et al [ 7 ] pointed out that healthy poultry responded positively to the inclusion of amino acids as feed additives and had an affirmative impact on performance.…”
Section: Introductionmentioning
confidence: 99%
“…Methionine is considered to play main roles in the body (Elnesr et al, 2019; Elwan et al, 2019), such as a glutathione precursor and reactive oxygen species elimination (Kidd, 2004). Methionine enhanced antibodies production and improved the level of immunoglobulins in serum (Rehman et al, 2019). Methionine has been reported to inhibit aflatoxicosis in broiler chickens (Yunianta, Agus, & Zuprizal, 2010).…”
Section: Introductionmentioning
confidence: 99%